2018
DOI: 10.1071/cp17287
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry, chemical composition and in vitro digestibility of sugarcane treated with calcium hydroxide

Abstract: Sugarcane is a source of roughage in animal feeding. It presents high production per unit of cultivated area, relatively easy cultivation and low cost of production per hectare, and better quality and a high dry matter (DM) yield in periods when forage is scarce. This study aimed to evaluate the effect of increasing levels of calcium hydroxide (Ca(OH)2) in sugarcane forage on chemical composition, in vitro digestibility values of DM, neutral detergent fibre (NDF) and acid detergent fibre (ADF), and kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Daur and Bakhashwain (2013) reported that humic acid 25 kg/ha had improved N, P, K, Ca, Mg and CP content in fodder maize. Several other studies also reported that the application of fertilizers (nitrate, urea, K and Ca) had improved the nutritional quality by reducing oxalic acid, an anti-nutritional compound (Dias et al, 2018;Jayanegara et al, 2017;Rahman & Kawamura, 2011). Chen et al (2017) reported that application of Mg fertilizer had improved pigment composition, root and shoot biomass; N, P and Mg contents; plant stoichiometry; the activity of arbuscular mycorrhizal fungi (AMF); and rhizobium in maize and soybean (Glycine max).…”
Section: Fertilization Applicationmentioning
confidence: 99%
“…Daur and Bakhashwain (2013) reported that humic acid 25 kg/ha had improved N, P, K, Ca, Mg and CP content in fodder maize. Several other studies also reported that the application of fertilizers (nitrate, urea, K and Ca) had improved the nutritional quality by reducing oxalic acid, an anti-nutritional compound (Dias et al, 2018;Jayanegara et al, 2017;Rahman & Kawamura, 2011). Chen et al (2017) reported that application of Mg fertilizer had improved pigment composition, root and shoot biomass; N, P and Mg contents; plant stoichiometry; the activity of arbuscular mycorrhizal fungi (AMF); and rhizobium in maize and soybean (Glycine max).…”
Section: Fertilization Applicationmentioning
confidence: 99%
“…This is because the addition of an alkaline agent, such as lime, for at least two hours, increases the pH up to 12 and maintains it constant for several days [9][10][11], altering the colloidal nature of pathogenic microorganisms' cellular protoplasm lethally [2]. In an agricultural context, alkalization with hydrated lime solubilizes structural carbohydrates and lignin from sugarcane (Saccharum officinarum) [12], caused by the thermo-decomposition process, verified by the energy release [13]. These processes speed up the mineralization of organic compounds during vermicomposting, while rapid changes in pH do not allow bacteria to adapt to this environment, impacting growth and spore formation and promoting its lethality [14].…”
Section: Introductionmentioning
confidence: 99%